ANGKA KECELAKAAN KERJA NAIK PENINGKATAN DALAM 8 TAHUN TERAKHIR : PENGIMPLEMENTASIAN PROGRAM ZERO ACCIDENT AWARD - Agris Bagus Puta Pratama; Galang Satrio Nugroho; Mardian Putra Frans (The Juris, 2024)
This research discusses important aspects in achieving complete mobility in a company, with a focus on labor aspects and Occupational Health and Safety (K3). Even though the company received the "Zero Accident Award" from the Ministry of Manpower for its success in achieving zero work accidents, the increase in the number of accidents in recent years shows the lack of success of this program. This research uses a qualitative approach with normative juridical analysis to identify gaps between regulations for implementing the Zero Accident Award program and field practice. The research results show the need for continuous improvement in risk management and work accident prevention in companies.